KAJIAN HUKUM TERHADAP PENYELESAIAN SENGKETA MEREK PADA POLO BY RALP LAUREN (Studi putusan No 83/Pdt.Sus-HKI/Merek2022/PN Niaga Jkt.Pst) - Aula Rifaldi, Risqi; Asi Islami, Trinah; Pratanto Rahayu , Wedi (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2023)
Settlement of disputes over the Polo by Ralph Laurem brand according to the commercial court decision no 83/pdt.sus- HKI/Merek2022//PN NiagaJkt.Pst. In this decision, the panel of judges stated that the plaintiff was the holder of the Polo by Ralph Lauren brand under list number 173934. Based on the decision it was proven that the defendant knew that the plaintiff was the owner of the trademark rights but the defendant ignored this fact and filed an application for brands in bad faith, namely by imitating the Plaintiff's Polo by Ralph Lauren brand. That based on the facts in the decision the defendant did not know. This type of research is normative juridical using secondary data as the main research data. The data were obtained from the Law on Trademarks and the decision of the Central Jakarta Commercial Court regarding the brand restriction and supplemented with secondary data in the form of books and articles with similar discussions. The data were collected using library techniques by reviewing the findings, analyzing and interpreting them based on the prepared theory. Data processing is done in a deductive way through propositions and theories that are general in nature led to specific facts so that they become a description that can be more easily understood. Court decision No 83/pdt.sus-HKI/Merek2022//PN NiagaJkt.Pst.. Established that the Central Jakarta Commercial Court In this decision, the panel of judges stated that the plaintiff was the holder of the Polo by Ralph Lauren trademark under register number 173934. Keywords : tradermark, Court decision, Polo by Ralp Lauren